Comparing the neuropsychiatric inventory and the revised memory and behavior problems checklist for associations with caregiver burden and depressive symptoms. (June 2014) - Jackson, Mark A.; Fauth, Elizabeth B.; Geiser, Christian
ABSTRACT Background: Few empirical studies compare the ability of prominent measures of behavioral and psychological symptoms of dementia (BPSD) to explain key caregiver outcomes. We compared the respective abilities of the Neuropsychiatric Inventory (NPI) and the Revised Memory and Behavior Problems Checklist (RMBPC) to detect associations between BPSD and caregiver depressive symptoms. Our results may facilitate measurement decisions for researchers and clinicians. Methods: The NPI and the RMBPC, which measure BPSD frequency and corresponding caregiver appraisals, were administered to 164 caregivers of persons with dementia to compare the measures' ability to explain caregiver depressive symptoms. Depressive symptoms were measured using the Geriatric Depression Scale (GDS), and caregiver burden was measured (using the Zarit Burden Interview) as a mediator between BPSD frequency/appraisal and caregiver depressive symptoms. Path analysis using Mplus facilitated the comparison between the RMBPC and the NPI. Results: Significant indirect associations were present when NPI frequency, NPI appraisal, RMBPC frequency, and RMBPC appraisal were modeled separately with burden and depressive symptoms, although indirect relationships are not associated with increases in R2. Only RMBPC appraisal produced both a significant direct association with depressive symptoms and a significant increase in R2 when modeled separately (β = 0.24, p < 0.01; ΔR2 = 0.04, p < 0.05). When all independent variables were modeled together, only RMBPC appraisal demonstrated significant direct (β = 0.23, p < 0.01) and indirect associations. Conclusion: The RMBPC might be more suitable than the NPI in studies measuring BPSD to explain key caregiver outcomes such as depressive symptoms.